QUANTITATIVE RELATIONSHIP OF ELECTRONIC STRUCTURE AND INHIBITION ACTIVITY OF CURCUMIN ANALOGS ON ETHOXYRESORUFIN o-DEALKYLATION (EROD) REACTION - Harno Dwi Pranowo; Iqmal Tahir; Ajidarma Widiatmoko (Universitas Gadjah Mada, 2007)
Electronic structure and inhibition activity relationship study of curcumin analogs has been established for 29 curcumin analogs on Ethoxyresorufin O-Dealkylation (EROD) reaction using atomic net charge descriptor based on AM1 semiempirical calculations. The QSAR (Quantitative Structure and Activities Relationships) equation model was determined by statistical parameter from multiple regression analysis and leave-one-out cross validation method. The best QSAR equation was described:log1/IC50 = (36.726±9.028) + (92.368±27.591)qC4 + (260.114±46.029)qC7 + (45.406±9.994)qC10 – (9.287±4.034)qC15 – (8.344±3.685)qC17 – (16.993±3.457)qC18 – (237.490±46.644)qO1 + (293.293±48.749)qO2